Positive electrode active material precursor, method for preparing same, method for preparing positive electrode active material using same,
By using lithium composite transition metal oxides in a single particle form with a molar ratio of lithium to all transition metals in the range of 0.01 to 0.7, and sintering at high temperature to prepare the positive electrode active material, the problems of small average particle size and low capacity retention rate of the single particle form of the positive electrode active material in the prior art are solved, and high energy density and excellent electrochemical performance are achieved.
Patent Information
- Application Number
- CN202380059605.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-02
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-18
AI Technical Summary
The positive electrode active materials of existing lithium secondary batteries are prone to oversintering during high-temperature heat treatment, resulting in a small average particle size in the form of single particles and the capacity retention rate of the battery has not been significantly improved.
Lithium composite transition metal oxides in the form of a single particle in the range of 0.01 to 0.7 were used as the precursor of the positive electrode active material, and were prepared by sintering at a temperature of 800°C to 1,200°C, combining appropriate particle density and particle size distribution to form a positive electrode active material with high single particle degree and narrow particle size distribution.
The capacity retention rate of the battery is improved, and high energy density and excellent electrochemical properties are achieved.
Smart Images

Figure CN119654715A_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of priority to Korean Patent Application No. 10-2022-0111520, filed on September 2, 2022, the disclosure of which is incorporated herein by reference. Technical Field
[0003] The present invention relates to a positive electrode active material precursor, a preparation method thereof, a method for preparing a positive electrode active material using the same, and a positive electrode active material. Background Art
[0004] Recently, with the increase in technology development and demand for mobile devices and electric vehicles, the demand for secondary batteries as energy sources has increased significantly. Among these secondary batteries, lithium secondary batteries with high energy density, high voltage, long cycle life and low self-discharge rate have been commercialized and widely used.
[0005] As positive electrode active materials for lithium secondary batteries, lithium transition metal oxides, for example, lithium cobalt oxides such as LiCoO 2 , lithium nickel oxide such as LiNiO 2 , lithium manganese oxides such as LiMnO 2 or LiMn 2 O 4 , or lithium iron phosphate such as LiFePO 4 Recently, lithium composite transition metal oxides containing two or more transition metals have been developed and widely used, for example, Li[Ni a Co b Mn c ]O 2 、Li[Ni a Co b Al c ]O 2 and Li[Ni a Co b Mn c Al d ]O 2 .
[0006] The lithium transition metal oxides developed so far are generally prepared by mixing a transition metal hydroxide with a lithium-containing raw material and then subjecting it to a high-temperature heat treatment. In this case, in order to prepare a lithium transition metal oxide in a single particle form having better strength and thermal stability than a lithium transition metal oxide in a secondary particle form, a method of slightly increasing the temperature during the high-temperature heat treatment is used.
[0007] However, in the case where a lithium transition metal oxide in single particle form is prepared by mixing a transition metal hydroxide with a lithium-containing raw material and then sintering (over-sintering) the mixture at a higher temperature than when preparing a conventional lithium transition metal oxide in secondary particle form, due to limitations in growing into a large-sized single particle form, the average particle size of the resulting single particle form of the positive electrode active material is not large, and there is a problem that the capacity retention rate of a battery containing the same is not significantly improved. Summary of the invention
[0008] Technical issues
[0009] One aspect of the present invention provides a cathode active material precursor capable of realizing a cathode active material in a single particle form that can improve the capacity retention rate of a battery.
[0010] Another aspect of the present invention provides a method for preparing a positive electrode active material precursor.
[0011] Another aspect of the present invention provides a method for preparing a positive electrode active material using the positive electrode active material precursor.
[0012] Another aspect of the present invention provides a positive electrode active material in the form of a single particle that can improve the capacity retention rate of a battery.
[0013] Technical Solution
[0014] The present invention provides a positive electrode active material precursor, a preparation method thereof, a method for preparing a positive electrode active material using the same, and a positive electrode active material.
[0015] (1) The present invention provides a positive electrode active material precursor comprising a lithium composite transition metal oxide in the form of a single particle in which the molar ratio of lithium to all transition metals (Li / Me) is in the range of 0.01 to 0.7, and
[0016] The particle density of the positive electrode active material precursor is 3.0 g / cm 3 Up to 4.0 g / cm 3 .
[0017] (2) The present invention provides the positive electrode active material precursor of (1) above, wherein the particle density is 3.4 g / cm 3 Up to 4.0 g / cm 3 within the range.
[0018] (3) The present invention provides a precursor of the positive electrode active material as described in (1) or (2) above, wherein the average particle diameter (D 50 ) of the lithium composite transition metal oxide in the form of single particles, where the molar ratio of lithium to all transition metals is in the range of 0.01 to 0.7, is 5.0 μm to 15.0 μm.
[0019] (4) The present invention provides a precursor of the positive electrode active material as described in any one of (1) to (3) above, wherein the lithium composite transition metal oxide in the form of single particles, where the molar ratio of lithium to all transition metals is in the range of 0.01 to 0.7, contains nickel at 60 mol% or more based on all transition metals other than lithium.
[0020] (5) The present invention provides a precursor of the positive electrode active material as described in any one of (1) to (4) above, wherein the lithium composite transition metal oxide in the form of single particles, where the molar ratio of lithium to all transition metals is in the range of 0.01 to 0.7, has a composition represented by Chemical Formula 1.
[0021] [Chemical Formula 1]
[0022] Li x Ni a M1 b M2 c O y
[0023] In Chemical Formula 1,
[0024] M1 is at least one selected from cobalt (Co), manganese (Mn), and aluminum (Al),
[0025] M2 is at least one selected from boron (B), magnesium (Mg), calcium (Ca), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), zinc (Zn), gallium (Ga), yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), tantalum (Ta), tungsten (W), sodium (Na), and lanthanum (La), and
[0026] 0.01 ≤ x ≤ 0.7, 0.60 ≤ a < 1.0, 0 < b ≤ 0.40, 0 ≤ c ≤ 0.1, 1 ≤ y ≤ 2 and a + b + c = 1.
[0027] (6) In addition, the present invention provides a method for preparing a precursor of a positive electrode active material, the method comprising the following steps:
[0028] (A) preparing a mixture by mixing a lithium-containing doping material with at least one selected from a composite transition metal hydroxide and a composite transition metal oxyhydroxide so that a molar ratio of lithium contained in the lithium-containing doping material to all transition metals contained in at least one selected from a composite transition metal hydroxide and a composite transition metal oxyhydroxide is in a range of 0.01 to 0.7; and
[0029] (B) A lithium composite transition metal oxide in the form of a single particle in which a molar ratio of lithium to all transition metals is in the range of 0.01 to 0.7 is prepared by sintering the mixture at a temperature of 800°C to 1,200°C.
[0030] (7) The present invention provides the method of (6) above, wherein the composite transition metal hydroxide and the composite transition metal oxyhydroxide contain 60 mol % or more of nickel based on all transition metals.
[0031] (8) The present invention provides the method of (6) or (7) above, wherein the lithium-containing doping material is at least one selected from lithium carbonate, lithium hydroxide, lithium oxide, lithium sulfate, lithium chloride, lithium nitrate, lithium acetate and lithium phosphate.
[0032] (9) The present invention provides the method according to any one of (6) to (8) above, wherein the sintering in step (B) is performed in air or an oxygen atmosphere.
[0033] (10) In addition, the present invention provides a method for preparing a positive electrode active material, the method comprising the following steps:
[0034] A lithium composite transition metal oxide in the form of single particles in which the molar ratio of lithium to all transition metals is in the range of 0.9 to 1.1 is prepared by mixing the positive electrode active material precursor of any one of (1) to (5) above with a lithium-containing raw material and sintering the mixture at a temperature of 700° C. to 1,100° C.,
[0035] The lithium-containing raw materials are mixed so that the molar ratio of all lithium contained in the positive electrode active material precursor and the lithium-containing raw materials to all transition metals except lithium contained in the positive electrode active material precursor is in the range of 0.9 to 1.1.
[0036] (11) The present invention provides the method of (10) above, wherein the sintering includes primary sintering at a temperature of 700°C to 1,100°C and then secondary sintering at a temperature of 650°C to 900°C.
[0037] (12) Furthermore, the present invention provides a positive electrode active material comprising a lithium composite transition metal oxide in the form of a single particle in which the molar ratio of lithium to all transition metals is in the range of 0.9 to 1.1,
[0038] The span value ([D 90 -D 10 / D 50 ) of the positive electrode active material is 0.800 to 1.00, and
[0039] the absolute value of the negative skewness of the positive electrode active material is 0.3000 to 0.7000.
[0040] (13) The present invention provides the positive electrode active material of the above (12), wherein the average particle diameter (D 50 ) of the lithium composite transition metal oxide in which the molar ratio of lithium to all transition metals is in the range of 0.9 to 1.1 is 5.0 μm to 15.0 μm.
[0041] (14) The present invention provides the positive electrode active material of any one of the above (12) or (13), wherein the lithium composite transition metal oxide in which the molar ratio of lithium to all transition metals is in the range of 0.9 to 1.1 contains 60 mol% or more of nickel based on all transition metals other than lithium.
[0042] (15) The present invention provides the positive electrode active material of any one of the above (12) to (14), wherein the lithium composite transition metal oxide in which the molar ratio of lithium to all transition metals is in the range of 0.9 to 1.1 has a composition represented by Chemical Formula 4.
[0043] [Chemical Formula 4]
[0044] Li x’ [Ni a’ M1 b’ M2 c’ O 2
[0045] In Chemical Formula 4,
[0046] M1 is at least one selected from cobalt (Co), manganese (Mn), and aluminum (Al),
[0047] M2 is at least one selected from boron (B), magnesium (Mg), calcium (Ca), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), zinc (Zn), gallium (Ga), yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), tantalum (Ta), tungsten (W), sodium (Na), and lanthanum (La), and
[0048] 0.9 ≤ x' ≤ 1.1, 0.6 ≤ a' < 1.0, 0 < b' ≤ 0.4, 0 < c' ≤ 0.1 and a' + b' + c' = 1.
[0049] Beneficial Effects
[0050] Since the positive electrode active material prepared using the positive electrode active material precursor according to the present invention has a single particle form with a high degree of single particle formation and a narrow particle size distribution, it can improve the capacity retention rate of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 (A) is a scanning electron microscope (SEM) image of the positive electrode active material precursor of Example 1, Figure 1 (B) is a SEM image of the positive electrode active material of Example 1.
[0052] Figure 2 (A) is a SEM image of the positive electrode active material precursor of Example 2, Figure 2 (B) is a SEM image of the positive electrode active material of Example 2.
[0053] Figure 3 (A) is a SEM image of the positive electrode active material precursor of Example 3, Figure 3 (B) is a SEM image of the positive electrode active material of Example 3.
[0054] Figure 4 (A) is a SEM image of the positive electrode active material precursor of Comparative Example 1, Figure 4 (B) is a SEM image of the positive electrode active material of Comparative Example 1.
[0055] Figure 5 (A) is a SEM image of the positive electrode active material precursor of Comparative Example 2, Figure 5 (B) is a SEM image of the positive electrode active material of Comparative Example 2.
[0056] Figure 6 (A) is a SEM image of the positive electrode active material precursor of Comparative Example 3, Figure 6 (B) is a SEM image of the positive electrode active material of Comparative Example 3.
[0057] Figure 7 (A) is a SEM image of the positive electrode active material precursor of Comparative Example 4, Figure 7 (B) is a SEM image of the positive electrode active material of Comparative Example 4.
[0058] Figure 8 D used in Examples 1 and 2 and Comparative Examples 1, 3 and 4 50 SEM image of the composite transition metal hydroxide at 9 μm. DETAILED DESCRIPTION
[0059] It should be understood that the words or terms used in this specification and claims should not be interpreted as being limited to the meanings defined in commonly used dictionaries, and it should also be understood that the words or terms should be interpreted as having meanings that are consistent with their meanings in the context of the relevant technical field and in the technical spirit of the present invention, based on the principle that the inventor can appropriately define the meanings of words or terms to best interpret the present invention.
[0060] It should also be understood that the terms "includes," "comprising," or "having" in this specification specify the presence of the stated features, numbers, steps, constituent elements, or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, constituent elements, or a combination thereof.
[0061] In this manual, D 10 , average particle size (D 50 ) and D 90 It can be defined as the particle size at which the cumulative volume is 10%, 50% and 90% in the particle size distribution curve (graphic curve of particle size distribution). 10 , average particle size (D 50 ) and D 90 This can be measured using laser diffraction. Laser diffraction can typically measure particle sizes from submicron to several mm, and can produce highly reproducible and high-resolution results. 10 , average particle size (D 50 ) and D 90 Specifically, PSA (Microtrac, S3500) can be used for measurement.
[0062] The term “on” in the present specification refers not only to a case where one constituent element is directly formed on an upper surface of another constituent element but also includes a case where an intervening constituent element may also exist.
[0063] In this specification, a single particle form is a concept in contrast to a spherical secondary particle form prepared by a conventional method and formed by agglomeration of tens to hundreds of primary particles, wherein the single particle form is a form in which particles are separated and / or dispersed from each other to form each particle's independent and / or separate phase, but may include a form in which 2 to 10 particles are attached to each other. That is, the single particle form may be a form consisting of only one particle or a form consisting of 2 to 10 primary particles.
[0064] In this specification, primary particles refer to the smallest unit particles observed during scanning electron microscopy (SEM) measurement. Secondary particles refer to aggregates in which primary particles constituting secondary particles are aggregated by physical or chemical bonding between primary particles without intentional aggregation or assembly process, that is, secondary structures.
[0065] In this specification, in a lithium composite transition metal oxide or a positive electrode active material in a single particle form, a high degree of single particle formation means that the number of primary particles constituting one particle is small from a morphological point of view, and the size of the primary particles is correspondingly large.
[0066] In this specification, an automatic pellet press (Carver, 3887.4) is used. After 3 g of a sample is placed in a pellet holder having a diameter of 13 mm and the zero point is adjusted, a force is applied until 2,000 kgf is reached. The pellet thickness in this case is measured to obtain the pellet volume, and the pellet density is a value calculated according to the following Mathematical Formula 1.
[0067] [Mathematical formula 1]
[0068] Particle density (g / cm 3 ) = positive electrode active material precursor weight (g) / particle volume (cm 3 )
[0069] In the present specification, the negative skewness of the positive electrode active material may be obtained by a method of calculating Pearson's asymmetry coefficient using a median value, and may be specifically obtained according to the following Mathematical Formula 2.
[0070] [Mathematical formula 2]
[0071] Negative skewness = [3 × (median - average particle size (D 50 ))] / (standard deviation)
[0072] In Mathematical Formula 2, the median is the data value corresponding to the center (middle) of all the data of the particle size distribution, the average particle size is as described above, and the standard deviation represents the degree of dispersion in the particle size distribution and refers to the degree of dispersion based on the mode. Median, average particle size (D 50 ) and standard deviation can be measured or calculated using PSA (Microtrac, S3500).
[0073] Positive electrode active material precursor
[0074] The positive electrode active material precursor according to the present invention comprises a lithium composite transition metal oxide in the form of a single particle in which the molar ratio of lithium to all transition metals (Li / Me) is in the range of 0.01 to 0.7, and the particle density of the positive electrode active material precursor is 3.0 g / cm 3 Up to 4.0 g / cm 3 .
[0075] As a result of extensive research to develop a single-particle positive electrode active material having a narrow particle size distribution and a high degree of single particleization, the present inventors have found that when a single-particle lithium composite transition metal oxide containing a lithium composite transition metal oxide having a molar ratio (Li / Me) of lithium to all transition metals in the range of 0.01 to 0.7 and a particle density of 3.0 g / cm 3 Up to 4.0 g / cm 3 When the positive electrode active material precursor is used as the positive electrode active material precursor, it is possible to prepare a positive electrode active material having a narrow particle size distribution and a high single particle degree and having various average particle sizes (D 50 ) in the form of a single particle positive electrode active material, thereby completing the present invention.
[0076] For the lithium composite transition metal oxide contained in the positive electrode active material precursor of the present invention, the molar ratio of lithium to all transition metals (Li / Me) satisfies 0.01 to 0.7, and due to the generated co-solvent effect (flux effect), the lithium composite transition metal oxide is in the form of a single particle. Specifically, the molar ratio of lithium to all transition metals (Li / Me) of the lithium composite transition metal oxide in the form of a single particle contained in the positive electrode active material precursor can be 0.01 or more, 0.03 or more, 0.3 or less, 0.5 or less, and 0.7 or less.
[0077] For lithium composite transition metal oxides in which the molar ratio of lithium to all transition metals (Li / Me) is less than 0.01, it is difficult to prepare a lithium composite transition metal oxide having an average particle size (D 50 ) is a positive electrode active material in the form of a single particle. In addition, for a lithium composite transition metal oxide in which the molar ratio of lithium to all transition metals (Li / Me) is greater than 0.7, it has a single particle form, but in this case, since the amount of lithium-containing raw materials that can be used in the process of preparing the positive electrode active material by mixing the positive electrode active material precursor with the lithium-containing raw materials according to the stoichiometric amount and then sintering is reduced, it is difficult to form a positive electrode active material with a stable structure, and as a result, the electrochemical performance may be reduced.
[0078] The particle density of the positive electrode active material precursor according to the present invention is 3.0 g / cm 3 Up to 4.0 g / cm 3 In this case, since the density of the positive electrode active material prepared by using the positive electrode active material precursor is high, particle breakage does not occur even when high pressure is applied during the rolling process during electrode manufacturing, thereby achieving high energy density. Specifically, the particle density of the positive electrode active material precursor can be 3 g / cm 3Above, 3.1 g / cm 3 Above, 3.2 g / cm 3 Above, 3.3g / cm 3 Above, 3.4 g / cm 3 Above, 3.8 g / cm 3 Below, 3.9 g / cm 3 Below and 4.0 g / cm 3 the following.
[0079] The particle density of the positive electrode active material precursor is less than 3.0 g / cm 3 In the case of the positive electrode active material prepared by using the positive electrode active material precursor, since the density is low, particle breakage is easily caused during the rolling process during electrode manufacturing, and a high energy density may not be achieved, and the particle density is greater than 4.0 g / cm 3 In the case of the positive electrode active material precursor, since the density of the positive electrode active material prepared by using the positive electrode active material precursor is too high, there is a problem that the positive electrode active material is not mixed with the conductive material during electrode preparation and agglomeration between positive electrode active material particles occurs.
[0080] According to the present invention, the average particle size (D) of the lithium composite transition metal oxide in the form of single particles in which the molar ratio of lithium to all transition metals (Li / Me) is in the range of 0.01 to 0.7 50 ) may be 5.0 μm to 15.0 μm. Specifically, the average particle size (D) of the lithium composite transition metal oxide in the form of a single particle in which the molar ratio of lithium to all transition metals (Li / Me) is in the range of 0.01 to 0.7 50 ) may be 5.0 μm or more, 6.0 μm or more, 7.0 μm or more, 8.0 μm or more, 12.0 μm or less, 13.0 μm or less, 14.0 μm or less, and 15.0 μm or less. In this case, since the density of the electrode including the positive electrode active material prepared by using the positive electrode active material precursor according to the present invention is high, a high energy density can be achieved.
[0081] According to the present invention, a lithium composite transition metal oxide in the form of a single particle in which the molar ratio of lithium to all transition metals (Li / Me) is in the range of 0.01 to 0.7 may contain 60 mol % or more of nickel based on all transition metals other than lithium, and specifically, may have a composition represented by the following Chemical Formula 1. In this case, due to the high nickel content, the potential of the positive electrode active material is reduced at the same voltage, so a high capacity can be achieved.
[0082] [Chemical formula 1]
[0083] Li x Nia M1 b M2 c O y
[0084] In Chemical Formula 1,
[0085] M1 is at least one selected from cobalt (Co), manganese (Mn), and aluminum (Al),
[0086] M2 is at least one selected from boron (B), magnesium (Mg), calcium (Ca), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), zinc (Zn), gallium (Ga), yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), tantalum (Ta), tungsten (W), sodium (Na), and lanthanum (La), and
[0087] 0.01 ≤ x ≤ 0.7, 0.60 ≤ a < 1.0, 0 < b ≤ 0.40, 0 ≤ c ≤ 0.1, 1 ≤ y ≤ 2 and a + b + c = 1.
[0088] Method for preparing positive electrode active material precursor
[0089] The method for preparing a precursor of a positive electrode active material according to the present invention includes the following steps:
[0090] (A) By mixing a lithium-containing doping material with at least one selected from a composite transition metal hydroxide and a composite transition metal hydroxyoxide, such that the molar ratio (Li / Me) of lithium contained in the lithium-containing doping material to all transition metals contained in at least one selected from a composite transition metal hydroxide and a composite transition metal hydroxyoxide is in the range of 0.01 to 0.7, thereby preparing a mixture; and
[0091] (B) By sintering the mixture at a temperature of 800 °C to 1,200 °C to prepare a lithium composite transition metal oxide in the form of single particles in which the molar ratio (Li / Me) of lithium to all transition metals is in the range of 0.01 to 0.7.
[0092] The precursor of a positive electrode active material prepared according to the method for preparing a precursor of a positive electrode active material may be the precursor of a positive electrode active material according to the present invention. That is, it may be a lithium composite transition metal oxide in the form of single particles in which the molar ratio (Li / Me) of lithium to all transition metals is in the range of 0.01 to 0.7, and the particle density is 3.0 g / cm 3 to 4.0 g / cm 3 of the precursor of a positive electrode active material.
[0093] The present inventors have found that the density of the oxide precursor prepared by adding a specific amount of lithium-containing doping material is higher than that of the conventional positive electrode active material precursor, and the positive electrode active material prepared by using the positive electrode active material precursor prepared according to the present invention is in the form of a single particle with a narrow particle size distribution and a high degree of single particleization, thereby completing the present invention.
[0094] Hereinafter, a method of preparing a positive electrode active material precursor will be described in detail with respect to each step.
[0095] Step (A)
[0096] Step (A) is a step of preparing a mixture by mixing a lithium-containing doping material with at least one selected from a composite transition metal hydroxide and a composite transition metal oxyhydroxide so that the molar ratio (Li / Me) of lithium contained in the lithium-containing doping material to all transition metals contained in at least one selected from a composite transition metal hydroxide and a composite transition metal oxyhydroxide is in the range of 0.01 to 0.7.
[0097] The present invention is characterized in that, in order to make the obtained positive electrode active material precursor contain a lithium composite transition metal oxide in the form of a single particle in which the molar ratio of lithium to all transition metals (Li / Me) is in the range of 0.01 to 0.7, a lithium-containing doping material is mixed with at least one selected from a composite transition metal hydroxide and a composite transition metal oxyhydroxide, so that the molar ratio (Li / Me) of lithium contained in the lithium-containing doping material to all transition metals contained in at least one selected from a composite transition metal hydroxide and a composite transition metal oxyhydroxide is in the range of 0.01 to 0.7.
[0098] When a lithium-doped material is mixed with at least one selected from a composite transition metal hydroxide and a composite transition metal hydroxyoxide such that the molar ratio (Li / Me) of lithium contained in the lithium-doped material to all transition metals contained in at least one selected from the composite transition metal hydroxide and the composite transition metal hydroxyoxide is less than 0.01, since primary particles do not grow significantly during sintering in step (B), oxides (precursors) in the form of single particles are not formed and there is a problem of the boundary of primary particles remaining. Further, when a lithium-doped material is mixed with at least one selected from a composite transition metal hydroxide and a composite transition metal hydroxyoxide such that the molar ratio (Li / Me) of lithium contained in the lithium-doped material to all transition metals contained in at least one selected from the composite transition metal hydroxide and the composite transition metal hydroxyoxide is greater than 0.7, for example, 0.9, oxides (precursors) in the form of single particles are prepared by sintering in step (B). However, in this case, since the amount of the lithium-containing raw material that can be used in the process of preparing the positive electrode active material by mixing the positive electrode active material precursor and the lithium-containing raw material stoichiometrically and then sintering is reduced, it is difficult to form a positive electrode active material with a stable structure. As a result, the electrochemical performance may be reduced.
[0099] According to the present invention, in order to achieve a high energy density, the composite transition metal hydroxide and the composite transition metal hydroxyoxide may contain 60 mol% or more of nickel based on all transition metals.
[0100] The composite transition metal hydroxide may have a composition represented by the following Chemical Formula 2, and the composite transition metal hydroxyoxide may have a composition represented by the following Chemical Formula 3.
[0101] [Chemical Formula 2]
[0102] Ni a2 M1 b2 M2 c2 (OH) 2
[0103] In Chemical Formula 2,
[0104] M1 is at least one selected from Co, Mn, and Al,
[0105] M2 is at least one selected from B, Mg, Ca, Ti, V, Cr, Fe, Zn, Ga, Y, Zr, Nb, Mo, Ta, W, Na, and La, and
[0106] 0.60 ≤ a2 < 1.0, 0 < b2 ≤ 0.40, 0 ≤ c2 ≤ 0.1 and a2 + b2 + c2 = 1.
[0107] [Chemical Formula 3]
[0108] Ni a2 M1 b2 M2 c2 O·OH
[0109] In Chemical Formula 3,
[0110] M1 is at least one selected from Co, Mn, and Al,
[0111] M2 is at least one selected from B, Mg, Ca, Ti, V, Cr, Fe, Zn, Ga, Y, Zr, Nb, Mo, Ta, W, Na, and La, and
[0112] 0.60 ≤ a2 < 1.0, 0 < b2 ≤ 0.40, 0 ≤ c2 ≤ 0.1 and a2 + b2 + c2 = 1.
[0113] According to the present invention, the lithium-containing doping material can be at least one selected from lithium carbonate, lithium hydroxide, lithium oxide, lithium sulfate, lithium chloride, lithium nitrate, lithium acetate, and lithium phosphate. Specifically, the lithium-containing doping material can be Li 2 CO 3 , LiOH, or a combination thereof.
[0114] Step (B)
[0115] Step (B) is a step of preparing a single-particle-form lithium composite transition metal oxide in which the molar ratio of lithium to all transition metals (Li / Me) is in the range of 0.01 to 0.7 by sintering the mixture at a temperature of 800 °C to 1,200 °C. If the mixture is sintered at a temperature of 800 °C to 1,200 °C, a single-particle-form lithium composite transition metal oxide in which the molar ratio of lithium to all transition metals (Li / Me) is in the range of 0.01 to 0.7 can be obtained. The sintering in Step (B) can specifically be carried out at the following temperatures: above 800 °C, above 850 °C, above 900 °C, above 950 °C, below 1,000 °C, below 1,050 °C, below 1,100 °C, below 1,150 °C, and below 1,200 °C.
[0116] In the case where the mixture is sintered at a temperature lower than 800 °C, since the lithium-containing doping material does not melt and remains on the surface, there is a problem that particle growth (expansion) does not occur. In the case where the mixture is sintered at a temperature higher than 1,200 °C, since the mixture is over-sintered, the phase of the lithium composite transition metal oxide becomes the most energy-stable NiO phase, and there is a problem that the NiO phase is difficult to recrystallize into an ideal layered structure. In addition, an alumina crucible, which is a commonly used crucible, may be modified, and as a result, an undesired material may be formed.
[0117] According to the present invention, the sintering in step (B) can be performed in air or oxygen atmosphere.
[0118] The sintering in step (B) may be performed for 1 hour to 20 hours.
[0119] Method for preparing positive electrode active material
[0120] The method for preparing a positive electrode active material according to the present invention includes the following steps: mixing a positive electrode active material precursor according to the present invention with a lithium-containing raw material so that the molar ratio of all lithium contained in the positive electrode active material precursor and the lithium-containing raw material to all transition metals other than lithium contained in the positive electrode active material precursor is in the range of 0.9 to 1.1, and then sintering the mixture at a temperature of 700° C. to 1,100° C. to prepare a lithium composite transition metal oxide in the form of a single particle in which the molar ratio of lithium to all transition metals (Li / Me) is in the range of 0.9 to 1.1. In this case, in the case where the sintering temperature is in the range of 700° C. to 1,100° C., the NiO phase can be stably recrystallized into a layered structure. In the case where the sintering temperature is less than 700° C. in the preparation of the positive electrode active material, there is a problem that recrystallization does not occur due to insufficient thermal energy, and in the case where the sintering temperature is greater than 1,100° C., there is a problem that a stable layered structure cannot be formed.
[0121] The lithium-containing raw material may be at least one selected from lithium carbonate, lithium hydroxide, lithium oxide, lithium sulfate, lithium chloride, lithium nitrate, lithium acetate, lithium phosphate and hydrates thereof. The lithium-containing raw material may specifically be at least one selected from lithium carbonate, lithium hydroxide, lithium oxide and hydrates thereof, and more specifically may be at least one selected from lithium carbonate, lithium hydroxide and hydrates thereof. In this case, the reactivity of the lithium-containing raw material with the precursor having a high atomic fraction of nickel among the metal elements in the precursor can be improved, and since the gas generated during the sintering process is CO 2 or H 2 O, so there is an advantage that the gas is harmless and can be easily removed.
[0122] According to the present invention, the lithium-containing raw material is mixed so that the molar ratio of the total lithium contained in the positive electrode active material precursor and the lithium-containing raw material to the total transition metals other than lithium contained in the positive electrode active material precursor is in the range of 0.9 to 1.1. In this case, since the structure of the resulting positive electrode active material becomes an ideal layered structure, the electrochemical performance can be excellent.
[0123] In the case where the lithium-containing raw material is mixed so that the molar ratio of the total lithium contained in the positive electrode active material precursor and the lithium-containing raw material to the total transition metals contained in the positive electrode active material precursor other than lithium is less than 0.9, due to the lack of lithium in the structure of the resulting positive electrode active material, the amount of lithium that can be reversibly moved is reduced, and as a result, problems may occur in electrochemical performance. In addition, in the case where the lithium-containing raw material is mixed so that the molar ratio of the total lithium contained in the positive electrode active material precursor and the lithium-containing raw material to the total transition metals contained in the positive electrode active material precursor other than lithium is greater than 1.1, since the residual lithium-containing raw material that has not reacted with the precursor exists on the surface of the positive electrode active material and acts as a lithium by-product, a gelation problem of the electrode slurry occurs during the preparation of the electrode, and there is a problem of increased gas generation of the battery.
[0124] According to the present invention, the sintering in the method for preparing a positive electrode active material may include performing a secondary sintering at a temperature of 700°C to 900°C after performing a primary sintering at a temperature of 800°C to 1,100°C. Specifically, the sintering may include: i) adjusting the temperature to 700°C to 900°C immediately after performing a primary sintering at a temperature of 800°C to 1,100°C, and performing a secondary sintering at a temperature of 700°C to 900°C, or ii) after performing a primary sintering at a temperature of 800°C to 1,100°C, lowering the temperature to room temperature, and raising the temperature again to perform a secondary sintering at a temperature of 700°C to 900°C. In this case, the secondary sintering temperature may be lower than the primary sintering temperature. In the case where the sintering is performed as in ii) above, more specifically, the sintering may include performing a secondary sintering at a temperature of 750°C to 850°C after pulverizing a primary sintering product prepared by performing a primary sintering at a temperature of 800°C to 1,000°C.
[0125] The sintering in the method for preparing the positive electrode active material can be performed in air or oxygen atmosphere. Therefore, the primary sintering and the secondary sintering can also be performed in air or oxygen atmosphere.
[0126] The sintering in the method for preparing the positive electrode active material can be performed for a sufficient time, specifically 3 to 20 hours, to form a stable layered structure. The primary sintering can be performed for 3 to 20 hours, and the secondary sintering can be performed for 3 to 20 hours.
[0127] The positive electrode active material prepared according to the method for preparing a positive electrode active material includes a lithium transition metal oxide in the form of a single particle in which the molar ratio of lithium to all transition metals (Li / Me) is in the range of 0.9 to 1.1, and can have a high degree of single particle while having a narrow particle size distribution.
[0128] The span value ([D90 -D 10 / D 50 ) may be from 0.800 to 1.00. Additionally, the absolute value of the negative skewness of the positive electrode active material prepared according to the method for preparing the positive electrode active material may be from 0.3000 to 0.7000. Furthermore, the positive electrode active material prepared according to the method for preparing the positive electrode active material may have a composition represented by Chemical Formula 4 below.
[0129] [Chemical Formula 4]
[0130] Li x’ [Ni a’ M1 b’ M2 c’ O 2
[0131] In Chemical Formula 4,
[0132] M1 is at least one selected from Co, Mn, and Al,
[0133] M2 is at least one selected from B, Mg, Ca, Ti, V, Cr, Fe, Zn, Ga, Y, Zr, Nb, Mo, Ta, W, Na, and La, and
[0134] 0.9 ≤ x’ ≤ 1.1, 0.6 ≤ a’ < 1.0, 0 < b’ ≤ 0.4, 0 < c’ ≤ 0.1 and a’ + b’ + c’ = 1.
[0135] Positive electrode active material
[0136] The positive electrode active material according to the present invention includes a single-particle lithium composite transition metal oxide in which the molar ratio of lithium to all transition metals (Li / Me) is in the range of 0.9 to 1.1, and the span value ([D 90 -D 10 / D 50 ) is from 0.800 to 1.00, and the absolute value of the negative skewness is from 0.3000 to 0.7000. Since the positive electrode active material has a narrow particle size distribution and a high degree of single-particle formation, the battery performance can be improved when used in a battery. In particular, the capacity retention rate can be further improved.
[0137] The positive electrode active material according to the present invention is a positive electrode active material prepared by using the positive electrode active material precursor according to the present invention, and it can be prepared by the method for preparing the positive electrode active material according to the present invention.
[0138] According to the present invention, the average particle size (D 50) can be from 7.0 μm to 13.0 μm. Specifically, the average particle diameter (D 50 ) of the single-particle form of the lithium composite transition metal oxide in which the molar ratio of lithium to all transition metals (Li / Me) is in the range of 0.9 to 1.1 can be 7.0 μm or more, 7.1 μm or more, 7.2 μm or more, 10.0 μm or less, 11.0 μm or less, 12.0 μm or less, and 13.0 μm or less. In this case, since the density of the electrode containing the positive electrode active material is high, a high energy density can be achieved.
[0139] According to the present invention, the lithium composite transition metal oxide in the form of single particles in which the molar ratio of lithium to all transition metals (Li / Me) is in the range of 0.9 to 1.1 can contain nickel of 60 mol% or more based on all transition metals other than lithium, and specifically can have a composition represented by the following Chemical Formula 4. In this case, due to the high nickel content, the potential of the positive electrode active material decreases at the same voltage, so a high capacity can be achieved.
[0140] [Chemical Formula 4]
[0141] Li x’ [Ni a’ M1 b’ M2 c’ O 2
[0142] In Chemical Formula 4,
[0143] M1 is at least one selected from Co, Mn, and Al,
[0144] M2 is at least one selected from B, Mg, Ca, Ti, V, Cr, Fe, Zn, Ga, Y, Zr, Nb, Mo, Ta, W, Na, and La, and
[0145] 0.9 ≤ x' ≤ 1.1, 0.6 ≤ a' < 1.0, 0 < b' ≤ 0.4, 0 < c' ≤ 0.1 and a' + b' + c' = 1.
[0146] positive electrode
[0147] In addition, the present invention can provide a positive electrode for a lithium secondary battery, and the positive electrode for a lithium secondary battery contains the positive electrode active material prepared by the above method.
[0148] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer provided on at least one surface of the positive electrode current collector and containing the above positive electrode active material.
[0149] There is no particular limitation on the positive electrode current collector as long as it has conductivity without causing adverse chemical changes in the battery, and for example: stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. In addition, the thickness of the positive electrode current collector can generally be 3 μm to 500 μm, and fine concavoconvexity can be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. For example, the positive electrode current collector can be used in various shapes such as a film, a sheet, a foil, a net, a porous body, a foam body, a non-woven fabric body, etc.
[0150] In addition to containing the positive electrode active material, the positive electrode active material layer may further contain a conductive material and a binder.
[0151] The positive electrode active material may be contained in an amount of 80 wt % to 99 wt %, more specifically 85 wt % to 98 wt %, based on the total weight of the positive electrode active material layer. When the content of the positive electrode active material is within the above range, excellent capacity characteristics may be obtained.
[0152] The conductive material is used to provide conductivity to the electrode, wherein any conductive material can be used without particular limitation, as long as it has suitable electronic conductivity without causing adverse chemical changes in the battery. Specific examples of conductive materials may be the following: graphite such as natural graphite or artificial graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and carbon fiber; powders or fibers of metals such as copper, nickel, aluminum and silver; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one thereof or a mixture of two or more thereof may be used. The content of the conductive material may be 1% to 30% by weight based on the total weight of the positive electrode active material layer.
[0153] The binder improves the adhesion between the positive active material particles and the adhesion between the positive active material and the collector. Specific examples of the binder can be: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof can be used. Based on the gross weight of the positive active material layer, the content of the binder can be 1% to 30% by weight.
[0154] In addition to using the above-mentioned positive electrode active materials, the positive electrode can be prepared according to a typical method for preparing a positive electrode. Specifically, a positive electrode active material layer-forming composition prepared by dissolving or dispersing a positive electrode active material and an optional binder and a conductive material in a solvent is coated on a positive electrode collector, and then the positive electrode can be prepared by drying and rolling the coated positive electrode collector. In this case, the type and amount of the positive electrode active material, binder and conductive material are the same as those described above.
[0155] The solvent may be a commonly used solvent in the art. The solvent may include dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone or water, and any one thereof or a mixture of two or more thereof may be used. If the coating thickness and manufacturing yield of the slurry are taken into account, the solvent may dissolve or disperse the positive electrode active material, the conductive material and the binder, and may be such that a viscosity having excellent thickness uniformity may be provided during subsequent coating of the positive electrode, the amount of the solvent may be sufficient.
[0156] Furthermore, as another method, the positive electrode may be prepared by casting the positive electrode active material layer-forming composition on a separate support and then laminating the film separated from the support on a positive electrode current collector.
[0157] Lithium secondary battery
[0158] In addition, in the present invention, an electrochemical device including the positive electrode can be prepared. The electrochemical device can be a battery or a capacitor, for example, a lithium secondary battery.
[0159] The lithium secondary battery specifically includes a positive electrode, a negative electrode disposed facing the positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte. Since the positive electrode is the same as described above, its detailed description will be omitted, and only the remaining configuration will be described in detail below.
[0160] In addition, the lithium secondary battery may further optionally include: a battery container accommodating an electrode assembly of a positive electrode, a negative electrode, and a separator; and a sealing member sealing the battery container.
[0161] In a lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector.
[0162] The negative electrode current collector is not particularly limited as long as it has high conductivity without causing adverse chemical changes in the battery, and for example: copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy can be used. In addition, the thickness of the negative electrode current collector can generally be 3 μm to 500 μm, and similar to the positive electrode current collector, fine concavoconvexity can be formed on the surface of the current collector to improve the adhesion of the negative electrode active material. For example, the negative electrode current collector can be used in various shapes such as a film, a sheet, a foil, a net, a porous body, a foam body, a non-woven fabric body, etc.
[0163] In addition to containing the negative electrode active material, the negative electrode active material layer may further contain a binder and a conductive material.
[0164] Compounds that can reversibly intercalate and deintercalate lithium can be used as negative electrode active materials. Specific examples of negative electrode active materials can be: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; (semi)metallic materials that can form alloys with lithium such as silicon (Si), aluminum (Al), tin (Sn), lead (Pb), zinc (Zn), bismuth (Bi), indium (In), magnesium (Mg), gallium (Ga), cadmium (Cd), Si alloys, Sn alloys, or Al alloys; (semi)metallic oxides that can be doped and dedoped with lithium such as SiO β (0<β<2), SnO 2 , vanadium oxide and lithium vanadium oxide; or a composite material comprising a (semi) metal material and a carbonaceous material such as a Si-C composite material or a Sn-C composite material, and any one thereof or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as a negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Typical examples of low-crystalline carbon can be soft carbon and hard carbon, and typical examples of high-crystalline carbon can be irregular, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite, pyrolytic carbon, mesophase pitch-type carbon fibers, mesophase carbon microbeads, mesophase pitch and high-temperature sintered carbon such as coke derived from petroleum or coal tar pitch.
[0165] The negative electrode active material may be contained in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.
[0166] The binder is a component that assists the bonding between the conductive material, the active material and the current collector, wherein the binder is generally added in an amount of 0.1 wt % to 10 wt % based on the total weight of the negative electrode active material layer. Examples of the binder may be polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber and various copolymers thereof.
[0167] The conductive material is a component for further improving the conductivity of the negative electrode active material, wherein the amount of the conductive material added may be 10% by weight or less, for example, 5% by weight or less, based on the total weight of the negative electrode active material layer. There is no particular limitation on the conductive material, as long as it has conductivity and does not cause adverse chemical changes in the battery, and for example, the following conductive materials may be used: graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers or metal fibers; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or polyphenylene derivatives.
[0168] The negative electrode active material layer can be prepared by coating a negative electrode material mixture prepared by dissolving or dispersing the negative electrode active material and optional binder and conductive material in a solvent on a negative electrode collector and drying the coated negative electrode collector, or can be prepared by casting the negative electrode material mixture on a separate support and then stacking a film separated from the support on the negative electrode collector.
[0169] In a lithium secondary battery, a separator separates the negative electrode from the positive electrode and provides a path for the movement of lithium ions, wherein any separator can be used as the separator without particular limitation, as long as it is commonly used in lithium secondary batteries, and in particular, a separator having high moisture retention capacity for electrolytes and low resistance to the movement of electrolyte ions can be used. Specifically, a porous polymer film, for example, a porous polymer film prepared from a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer; or a laminated structure having two or more layers thereof can be used. In addition, a typical porous non-woven fabric can be used, such as a non-woven fabric formed of a high melting point glass fiber or a polyethylene terephthalate fiber. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a single-layer or multilayer structure can be optionally used.
[0170] In addition, the electrolyte used in the present invention may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte or a molten inorganic electrolyte that can be used in the preparation of a lithium secondary battery, but the present invention is not limited thereto.
[0171] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0172] Any organic solvent can be used as the organic solvent without particular limitation, as long as it can be used as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, the following substances can be used as organic solvents: ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; or carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitrile such as R-CN (wherein R is a linear, branched or cyclic C2-C20 hydrocarbon group and may contain a double bond, an aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; or cyclopentane sulfone. Among these solvents, carbonate solvents are preferred, and a mixture of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant and a linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) having low viscosity that can improve the charge and discharge performance of the battery is more preferred. In this case, when the cyclic carbonate is mixed with the chain carbonate in a volume ratio of about 1:1 to about 1:9, the performance of the electrolyte can be excellent.
[0173] The lithium salt can be used without particular limitation as long as it is a compound that can provide lithium ions used in a lithium secondary battery. Specifically, the following substances can be used as the lithium salt: LiPF 6 、LiClO 4 、LiAsF 6 , LiBF 4 、LiSbF 6 、LiAlO 4 、LiAlCl 4 、LiCF 3 SO 3 ,LiC 4 F 9 SO 3 、LiN(C 2 F 5 SO 3 ) 2 、LiN(C 2 F 5SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 , LiCl, LiI or LiB(C 2 O 4 ) 2 The lithium salt may be used in a concentration range of 0.1 M to 2.0 M. In the case where the concentration of the lithium salt is included in the above range, since the electrolyte may have appropriate conductivity and viscosity, excellent electrolyte performance may be obtained, and lithium ions may be efficiently moved.
[0174] In order to improve the life characteristics of the battery, suppress the reduction of the battery capacity and improve the discharge capacity of the battery, in addition to the electrolyte components, at least one additive can be added to the electrolyte, such as a halogenated alkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, (condensed) glycol dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinone, N, N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum chloride. In this case, based on the total weight of the electrolyte, the content of the additive can be 0.1% by weight to 5% by weight.
[0175] As described above, since the lithium secondary battery including the cathode active material according to the present invention stably exhibits excellent cycle characteristics, the lithium secondary battery is suitable for portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).
[0176] Thus, a battery module including the lithium secondary battery as a unit cell and a battery pack including the battery module are provided.
[0177] The battery module or battery pack may be used as a power source for at least one of the following medium to large devices: a power tool; an electric vehicle, including an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.
[0178] The shape of the lithium secondary battery of the present invention is not particularly limited, but a cylindrical type using a can, a square type, a pouch type, or a coin type can be used.
[0179] The lithium secondary battery according to the present invention can be used not only in a battery cell as a power source for small devices but also as a unit battery in a medium or large battery module including a plurality of battery cells.
[0180] Preferred Embodiments
[0181] Hereinafter, embodiments of the present invention will be described in detail in a manner that allows those skilled in the art to which the present invention belongs to easily implement the present invention. However, the present invention can be embodied in many different forms and should not be construed as being limited to the embodiments set forth herein.
[0182] Examples and Comparative Examples
[0183] Example 1
[0184] By using an acoustic mixer, the Ni 0.96 Co 0.03 Mn 0.01 (OH) 2 The composite transition metal hydroxide (D 50 : 9 μm) was mixed with LiOH as a lithium-containing dopant material so that the molar ratio (Li / Me) of lithium (Li) contained in LiOH to all transition metals (Me) contained in the composite transition metal hydroxide was 0.3, thereby preparing a mixture.
[0185] The mixture was sintered at 1,020°C for 9 hours in an air atmosphere to prepare a Li 0.3 Ni 0.96 Co 0.03 Mn 0.01 O 1.3 A lithium composite transition metal oxide in the form of a single particle (hereinafter, referred to as a positive electrode active material precursor A) having a composition represented by .
[0186] The positive electrode active material precursor A was mixed with LiOH so that the molar ratio (Li' / Me') of all lithium contained in the positive electrode active material precursor and LiOH to all transition metals (Me') contained in the positive electrode active material precursor other than lithium was 1.0, and the mixture was primarily sintered at 830° C. for 12 hours in an oxygen atmosphere, then pulverized using a jet mill, and secondary sintered at 770° C. for 12 hours in an oxygen atmosphere to prepare a LiNi 0.96 Co 0.03 Mn 0.01 O 2 The composition of the lithium composite transition metal oxide in the form of a single particle, ie, the positive electrode active material A, is represented.
[0187] For reference, the number of moles of all lithium contained in the positive electrode active material precursor and LiOH is the sum of the number of moles of lithium contained in the positive electrode active material precursor and the number of moles of lithium contained in LiOH.
[0188] Example 2
[0189] With Li 0.5 Ni0.96 Co 0.03 Mn 0.01 O 1.5 A lithium composite transition metal oxide in the form of a single particle of a composition represented by 0.96 Co 0.03 Mn 0.01 (OH) 2 The composite transition metal hydroxide (D 50 : 9 μm) was mixed with LiOH as a lithium-containing doping material so that the molar ratio (Li / Me) of lithium contained in LiOH to all transition metals contained in the composite transition metal hydroxide was 0.5, thereby preparing a mixture.
[0190] With LiNi 0.96 Co 0.03 Mn 0.01 O 2 A lithium composite transition metal oxide in the form of a single particle having a composition shown, that is, a positive electrode active material B was prepared in the same manner as in Example 1, except that the positive electrode active material precursor B was used.
[0191] Example 3
[0192] With Li 0.3 Ni 0.96 Co 0.03 Mn 0.01 O 1.3 A lithium composite transition metal oxide in the form of a single particle of a composition represented by 0.96 Co 0.03 Mn 0.01 (OH) 2 The composite transition metal hydroxide (D 50 : 6 μm) was mixed with LiOH as a lithium-containing doping material so that the molar ratio (Li / Me) of lithium contained in LiOH to all transition metals contained in the composite transition metal hydroxide was 0.3, thereby preparing a mixture.
[0193] With LiNi 0.96 Co 0.03 Mn 0.01 O 2 A lithium composite transition metal oxide in the form of a single particle having a composition shown, that is, a positive electrode active material C was prepared in the same manner as in Example 1, except that the positive electrode active material precursor C was used.
[0194] Comparative Example 1
[0195] The Ni 0.96 Co 0.03 Mn 0.01 (OH) 2 The composite transition metal hydroxide (D 50 :9 μm) for 9 hours to prepare a Ni 0.96 Co 0.03 Mn 0.01 A composite transition metal oxide of a composition represented by O (hereinafter, referred to as a positive electrode active material precursor D).
[0196] The positive electrode active material precursor D was mixed with LiOH so that the molar ratio (Li' / Me') of lithium contained in LiOH to all transition metals contained in the positive electrode active material precursor except lithium was 1.0, and the mixture was primarily sintered at 830° C. for 12 hours in an oxygen atmosphere, then pulverized using a jet mill, and secondary sintered at 770° C. for 12 hours in an oxygen atmosphere to prepare a LiNi 0.96 Co 0.03 Mn 0.01 O 2 The composition of the lithium composite transition metal oxide in the form of a single particle, ie, the positive electrode active material D, is represented.
[0197] Comparative Example 2
[0198] The Ni 0.96 Co 0.03 Mn 0.01 (OH) 2 The composite transition metal hydroxide (D 50 :6 μm) for 9 hours to prepare a Ni 0.96 Co 0.03 Mn 0.01 A composite transition metal oxide of a composition represented by O (hereinafter, referred to as a positive electrode active material precursor E).
[0199] The positive electrode active material precursor E was mixed with LiOH so that the molar ratio (Li' / Me') of lithium contained in LiOH to all transition metals contained in the positive electrode active material precursor except lithium was 1.0, and the mixture was primarily sintered at 830° C. for 12 hours in an oxygen atmosphere, then pulverized using a jet mill, and secondary sintered at 770° C. for 12 hours in an oxygen atmosphere to prepare a LiNi 0.96 Co 0.03 Mn 0.01 O2 The composition of the lithium composite transition metal oxide in the form of a single particle, ie, the positive electrode active material E is represented.
[0200] Comparative Example 3
[0201] With Li 0.005 Ni 0.96 Co 0.03 Mn 0.01 O 1.005 A lithium composite transition metal oxide in the form of a single particle of a composition represented by 0.96 Co 0.03 Mn 0.01 (OH) 2 The composite transition metal hydroxide (D 50 :9 μm) was mixed with LiOH as a lithium-containing doping material so that the molar ratio (Li / Me) of lithium contained in LiOH to all transition metals contained in the composite transition metal hydroxide was 0.005, thereby preparing a mixture.
[0202] With LiNi 0.96 Co 0.03 Mn 0.01 O 2 A lithium composite transition metal oxide in the form of a single particle having a composition shown, that is, a positive electrode active material F was prepared in the same manner as in Example 1, except that the positive electrode active material precursor F was used.
[0203] Comparative Example 4
[0204] With Li 0.9 Ni 0.96 Co 0.03 Mn 0.01 O 1.9 A lithium composite transition metal oxide in the form of a single particle of a composition represented by 0.96 Co 0.03 Mn 0.01 (OH) 2 The composite transition metal hydroxide (D 50 :9 μm) was mixed with LiOH as a lithium-containing doping material so that the molar ratio (Li / Me) of lithium contained in LiOH to all transition metals contained in the composite transition metal hydroxide was 0.9, thereby preparing a mixture.
[0205] With LiNi0.96 Co 0.03 Mn 0.01 O 2 A lithium composite transition metal oxide in the form of a single particle having a composition shown, that is, a positive electrode active material G was prepared in the same manner as in Example 1, except that the positive electrode active material precursor G was used.
[0206] Experimental example
[0207] Experimental Example 1
[0208] Scanning electron microscope (SEM) images of each positive electrode active material precursor and positive electrode active material of Examples 1 to 3 and Comparative Examples 1 to 4 were measured using SEM (FEI, Inspect F) and are shown in FIG. Figures 1 to 7 In addition, the D used in Examples 1 and 2 and Comparative Examples 1, 3 and 4 was measured. 50 The SEM image of the composite transition metal hydroxide is 9 μm and is shown in Figure 8 middle.
[0209] Experimental Example 2
[0210] Using an automatic pellet press (Carver, 3887.4), 3 g of each of the positive electrode active material precursors of Examples 1 to 3 and Comparative Examples 1 to 4 were collected, placed in a pellet holder with a diameter of 13 mm and the zero point was adjusted, and a force was applied until it reached 2,000 kgf. The thickness in this case was measured to obtain the particle volume, and then the particle density was calculated according to the following mathematical formula 1 and presented in the following Table 1.
[0211] [Mathematical formula 1]
[0212] Particle density (g / cm 3 ) = positive electrode active material precursor weight (g) / particle volume (cm 3 )
[0213] Experimental Example 3
[0214] The average particle size (D 50 ), and are presented in Table 1 below.
[0215] In addition, the D values of the positive electrode active materials of Examples 1 to 3 and Comparative Examples 1 to 4 were obtained. 10 , average particle size (D 50 )、D 90 and negative skewness, and the average particle size (D 50 ), span values and the absolute values of negative skewness are presented in Table 1 below.
[0216]
[0217] Experimental Example 4
[0218] Each positive electrode active material prepared in Examples 1 to 3 and Comparative Examples 1 to 4, a carbon black conductive material, and a polyvinylidene fluoride (PVDF) binder were mixed in an N-methylpyrrolidone (NMP) solvent at a weight ratio of 96:2:2 to prepare a positive electrode slurry. One surface of an aluminum current collector was coated with the positive electrode slurry, dried at 130°C, and then rolled to prepare each positive electrode.
[0219] A lithium metal electrode was used as a negative electrode, an electrode assembly was prepared by placing a porous polyethylene separator between the positive electrode and the negative electrode, the electrode assembly was placed in a battery case, and then an electrolyte was injected into the battery case to prepare a half-cell. In this case, the electrolyte was prepared by dissolving 1.0 M LiPF in an organic solvent in which ethylene carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) were mixed in a volume ratio of 3:4:3. 6 Prepared.
[0220] Each half cell thus prepared was charged to 4.25 V at a constant current / constant voltage (CC / CV) rate of 0.1 C at 25°C, and discharged to 2.5 V at a rate of 0.1 C to measure the initial charge capacity and the initial discharge capacity, and the initial efficiency was calculated and presented in the following Table 2. For reference, the initial efficiency value is the percentage of the initial discharge capacity to the initial charge capacity.
[0221] In addition, the capacity of the lithium secondary battery was measured by repeating a charge and discharge cycle of charging at a 0.5 C rate and discharging at a 1.0 C rate in the range of 2.5 V to 4.25 V at 45°C for 50 times, and the percentage of the discharge capacity of the 50th cycle to the discharge capacity of the 1st cycle was set as the capacity retention rate, and the capacity retention rate is presented in Table 2 below.
[0222]
[0223] Referring to the SEM images and Tables 1 and 2, a lithium composite transition metal oxide in the form of single particles in which the molar ratio of lithium to all transition metals (Li / Me) is in the range of 0.01 to 0.7 and the particle density is 3.0 g / cm 3 Up to 4.0g / cm 3 When the positive electrode active material precursor is used as the positive electrode active material precursor, it can be understood that a plurality of particles having a narrow particle size distribution and a high degree of single particle formation and having various average particle sizes (D 50) single particle form of positive electrode active material. In addition, since the positive electrode active materials of Examples 1 to 3 have a narrow particle size distribution and a high degree of single particleization, it can be understood that when used in a battery, they can improve the performance of the battery, especially the capacity retention rate.
[0224] Specifically, it was confirmed that by using a lithium composite transition metal oxide in the form of a single particle in which the molar ratio of lithium to all transition metals (Li / Me) is in the range of 0.01 to 0.7 and the particle density is 3.0 g / cm 3 Up to 4.0 g / cm 3 The positive electrode active materials of Examples 1 and 2 prepared by using the positive electrode active material precursor of 0.01% to 0.7% have better capacity retention than the positive electrode active material of Comparative Example 1 due to the improvement of the single particle degree. In addition, it can be confirmed that by using a lithium composite transition metal oxide in the form of a single particle in which the molar ratio of lithium to all transition metals (Li / Me) is in the range of 0.01 to 0.7 and the particle density is 3.0 g / cm 3 Up to 4.0 g / cm 3 The positive electrode active material of Example 3 prepared by using the positive electrode active material precursor has a better capacity retention rate than the positive electrode active material of Comparative Example 2 due to the improvement of the single particle degree.
[0225] In addition, since the positive electrode active materials of Examples 1 and 2 have a higher single particle degree than the positive electrode active material of Comparative Example 3 prepared by using a lithium composite transition metal oxide having a molar ratio (Li / Me) of lithium to all transition metals of 0.005, it can be confirmed that both the initial efficiency and the capacity retention rate are significantly excellent. In addition, since the positive electrode active materials of Examples 1 and 2 have a higher structural stability and a higher single particle degree than the positive electrode active material of Comparative Example 4 prepared by using a lithium composite transition metal oxide having a molar ratio (Li / Me) of lithium to all transition metals of 0.9, it can be confirmed that both the initial efficiency and the capacity retention rate are significantly excellent.
Claims
1. A precursor of a cathode active material, the precursor of the cathode active material comprising a lithium composite transition metal oxide in the form of single particles, wherein the molar ratio of lithium to all transition metals (Li / Me) is in the range of 0.01 to 0.7, and The particle density of the positive electrode active material precursor is 3.0 g / cm 3 Up to 4.0 g / cm 3 .
2. The positive electrode active material precursor according to claim 1, wherein The particle density is 3.4 g / cm 3 Up to 4.0 g / cm 3 within the range.
3. The positive electrode active material precursor according to claim 1, wherein The average particle size (D) of the lithium composite transition metal oxide in the form of a single particle in which the molar ratio of lithium to all transition metals is in the range of 0.01 to 0.7 50 ) is 5.0 μm to 15.0 μm.
4. The positive electrode active material precursor according to claim 1, wherein the lithium composite transition metal oxide in the form of single particles, wherein the molar ratio of lithium to all transition metals is in the range of 0.01 to 0.7, contains 60 mol% or more of nickel based on all transition metals other than lithium.
5. The positive electrode active material precursor according to claim 1, wherein The lithium composite transition metal oxide in the form of single particles, wherein the molar ratio of lithium to all transition metals is in the range of 0.01 to 0.7, has a composition represented by Chemical Formula 1: [Chemical Formula 1] Li x Ni a M1 b M2 c O y Wherein, in Chemical Formula 1, M1 is at least one selected from Co, Mn, and Al, M2 is at least one selected from B, Mg, Ca, Ti, V, Cr, Fe, Zn, Ga, Y, Zr, Nb, Mo, Ta, W, Na, and La, and 0.01 ≤ x ≤ 0.7, 0.60 ≤ a < 1.0, 0 < b ≤ 0.40, 0 ≤ c ≤ 0.1, 1 ≤ y ≤ 2 and a + b + c = 1.
6. A method for preparing a precursor of a cathode active material, the method comprising the following steps: (A) Preparing a mixture by mixing a lithium-doped material with at least one selected from a composite transition metal hydroxide and a composite transition metal hydroxy-oxide, such that the molar ratio of lithium contained in the lithium-doped material to all transition metals contained in at least one selected from the composite transition metal hydroxide and the composite transition metal hydroxy-oxide is in the range of 0.01 to 0.7; and (B) Preparing a lithium composite transition metal oxide in the form of single particles, wherein the molar ratio of lithium to all transition metals is in the range of 0.01 to 0.7, by sintering the mixture at a temperature of 800 °C to 1,200 °C.
7. The method according to claim 6, wherein: The composite transition metal hydroxide and the composite transition metal hydroxy-oxide contain 60 mol% or more of nickel based on all transition metals.
8. The method according to claim 6, wherein: The lithium-doped material is at least one selected from lithium carbonate, lithium hydroxide, lithium oxide, lithium sulfate, lithium chloride, lithium nitrate, lithium acetate, and lithium phosphate.
9. The method according to claim 6, wherein: The sintering in step (B) is carried out in an air or oxygen atmosphere.
10. A method for preparing a positive electrode active material, the method comprising the following steps: By mixing the precursor of the cathode active material according to any one of claims 1 to 5 with a lithium-containing raw material and sintering the mixture at a temperature of 700 °C to 1,100 °C, a lithium composite transition metal oxide in the form of single particles, wherein the molar ratio of lithium to all transition metals is in the range of 0.9 to 1.1, is prepared, wherein the lithium-containing raw material is mixed such that the molar ratio of all lithium contained in the precursor of the cathode active material and the lithium-containing raw material to all transition metals other than lithium contained in the precursor of the cathode active material is in the range of 0.9 to 1.
1.
11. The method according to claim 10, wherein: The sintering includes: after performing primary sintering at a temperature of 800 °C to 1,100 °C, performing secondary sintering at a temperature of 700 °C to 900 °C.
12. A positive electrode active material, which comprises a lithium composite transition metal oxide in the form of single particles, in which the molar ratio of lithium to all transition metals is in the range of 0.9 to 1.
1. The span value ([D 90 -D 10 ] / D 50 ) is 0.800 to 1.00, and The absolute value of the negative skewness of the positive electrode active material is 0.3000 to 0.7000.
13. The positive electrode active material according to claim 12, wherein The average particle size (D 50 ) is 5.0 μm to 15.0 μm.
14. The positive electrode active material according to claim 12, wherein The lithium composite transition metal oxide in which the molar ratio of lithium to all transition metals is in the range of 0.9 to 1.1 contains nickel of 60 mol% or more based on all transition metals other than lithium.
15. The positive electrode active material according to claim 12, wherein The lithium composite transition metal oxide in which the molar ratio of lithium to all transition metals is in the range of 0.9 to 1.1 has a composition represented by Chemical Formula 4: [Chemical Formula 4] The x’ [Nor a’ M1 b’ M2 c’ ]O2 Wherein, in Chemical Formula 4, M1 is at least one selected from Co, Mn and Al, M2 is at least one selected from B, Mg, Ca, Ti, V, Cr, Fe, Zn, Ga, Y, Zr, Nb, Mo, Ta, W, Na and La, and 0.9 ≤ x' ≤ 1.1, 0.6 ≤ a' < 1.0, 0 < b' ≤ 0.4, 0 < c' ≤ 0.1 and a' + b' + c' = 1.
Citation Information
Patent Citations
Composition for preventing or treating of sepsis comprising Hederacolchiside E
KR1020220111520A